Prognostic significance of postoperative loss of skeletal muscle mass in patients underwent coronary artery bypass grafting - Shen, Zi-Le; Liu, Zhang; Zhang, Peng; Chen, Wei-Zhe; Dong, Wen-Xi; Chen, Wen-Hao; Lin, Feng; Zang, Wang-Fu; Yan, Xia-Lin; Yu, Zhen (Frontiers in Nutrition, 2022)
Background: Increasing life expectancy of coronary artery bypass grafting (CABG) remains to be the major concern of cardiac surgeons. However, few studies have investigated the effect of postoperative skeletal muscle index (SMI) loss on prognosis. This study aims to evaluate the prognostic role of postoperative SMI loss ≥ 5 % after CABG, in order to develop a novel nomogram to predict overall survival (OS). Methods: Patients underwent CABG via midline sternotomy from December 2015 to March 2021 were recruited in this study. Preoperative and postoperative 3 months chest computed tomography images were compared to assess changes in SMI at T12 level. Based on this, patients were classified into the presence or absence of SMI loss ≥ 5%. The association between postoperative SMI loss ≥ 5 % and OS was then analyzed by the Kaplan-Meier curves and Cox model. A novel nomogram incorporating independent clinical prognostic variables was also developed. Results: The study enrolled 506 patients receiving CABG, of whom 98 patients experienced T12 SMI loss ≥ 5% and had a significantly worse OS (P < 0.0001). Multivariate regression analysis showed that T12 SMI per cent change (%T12 SMI-change) was an independent prognostic factor for OS (HR = 0.809, 95% CI = 0.749 to 0.874). The nomogram incorporating %T12 SMI-change with other variables was accurate for predicting OS. Besides, we also found that postoperative oral nutritional supplement can rescue T12 SMI loss. Conclusions: Postoperative SMI loss can predict survival outcome after CABG. The nomogram incorporating changes in SMI provides a superior performance than existing systems.